International competitiveness and knowledge-based industries in India - Kumar, Nagesh 1958 -; Joseph, K. J. 1961 - (New Delhi : Oxford University Press, 2007)
Contributed articles with reference to electronics, pharmaceutical, chemical automotive and non-electrical machinery industries in India
The book is an outcome of a major study undertaken at Research and Information System for developing countries
Includes bibliographical references
Keywords: Manufacturing industries -- Technological innovations -- India -- Management; Foreign trade promotion -- India; Terms of trade -- India; Industrial policy -- India